The Theory of Capital and the Role of Voluntary Savings on Comparative Advantages of Creation in Intensive Capital Goods - Silva, Felipe Rosa da; Branda, Domingos Crosseti; Feistel, Paulo Ricardo (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
The article aims to demonstrate the role of voluntary private savings in the capital accumulation process. For such is exposed, first, the capital of the theory developed by Carl Menger, Böhm-Bawerk and Friedrich Hayek perfected by for later focus on the key role of voluntary private savings as generating element of the necessary capital accumulation to make more capital-intensive economies. The argument revolves around the Ricardo effect and, subsequently, the advantages in specializing in input where a country is abundant. The main theoretical finding focuses on the possibility of creating comparative advantages in capital goods (via voluntary savings) indicating an important theoretical postulate for those countries seeking to industrialize and achieve greater competitive insertion in the international market.